The Effect Size of Implementing Physics Textbook Using Multimodal Representations - Merta Simbolon,; Anderias Henukh,; Don Jaya Putra,; Dimas Frananta Simatupang, (Technium Social Sciences Journal, 2023)
This study aims to determine the effect size of implementing a physics textbook developed using multimodal representations to enhance the cognitive abilities and problem-solving skills of students. The research was conducted in one of the high schools in Bandung city with a sample size of 69 students. The sampling technique used was the class random technique. The sample was divided into two groups: the control group and the experimental group. In the control group, students learned using their regular textbooks, while in the experimental group, they used the textbook developed using multimodal representations and the Rosengrant problem-solving stages. The implementation of the textbooks in both the control and experimental groups was conducted using the PQ4R method (Preview, Question, Read, Reflect, Recite, Review) to focus the results solely on the influence of the textbooks. The results obtained indicate that the implementation of the developed textbook in this study had a significant impact on the cognitive abilities and problem-solving skills of the students.